Multiplicative Schwarz Algorithm with Time Stepping Along Characteristic for Convection Diffusion Equations (Journal of Computational Mathematics, 2001)
Based on domain decomposition, we give two multiplicative schwarz methods with time stepping along characteristic for semi-linear, convection diffusion parabolic problems. We give some a priori error estimates, which tell us that the convergence of the approximate solution is independent of the iteration times at every time-level. Finally we give some numerical examples.
Keywords: Multiplicative Schwarz method; Convection diffusion equation; Characteristic; Error estimation.